Identification of physical occupational hazards and proposals for preventive measures at the warehouse keeper's workplace - Anna Kowalczyk; Izabela Chodoła; Kinga Kulczycka; Ewa Stychno (Kazimierz Wielki University, 2018)
Warehouse keeper is a person responsible in the workplace for receiving goods into the warehouse, storing stored goods, maintaining the identification system adopted and picking and releasing goods from the warehouse. At the time of receipt of goods, he makes a quantitative and qualitative acceptance. It then ensures appropriate storage conditions for the given type of goods and decides on the location of the goods in the storage rooms. The stored goods protect against damage, spoilage, destruction and theft. He is financially responsible for the goods and resources entrusted to him. Depending on the type of goods stored, the conditions prevailing in storage rooms may be onerous (open, closed, above-ground or underground rooms, heated or cooled, ventilated or humidified, etc. ). The warehouse keeper usually works in one-shift system, but sometimes the nature of the company requires work in shifts, day and night, on public holidays. A warehouse keeper is exposed to a wide range of occupational hazards, from physical, chemical, biological and psychosocial. The aim of this work is to identify physical occupational hazards and to propose preventive measures at the warehouse keeper's workplace.